Atypical Regressive Corneal Endothelial Cysts in Long-Term Confocal Follow-Up: A Case Report. Issue 9 (March 2015) - Smedowski, Adrian; Wylegala, Edward; Wojcik, Lukasz; Tarnawska, Dorota
Abstract : Abstract: Corneal endothelium is formed of 1 layer of mitochondria-rich cubic cells whose main role is to maintain corneal transparency. Corneal endothelial disorders represent group of both inherited and noninherited and may affect proper vision. A 36-year-old male patient with suspicion of corneal endothelial dystrophy underwent visual acuity, intraocular pressure, the basic slit-lamp examination, anterior segment optical coherence tomography (AS-OCT) (Visante, Carl Zeiss Meditec, Dublin, CA), and corneal confocal microscopy in vivo (Rostock Cornea Module, Heidelberg Engineering Retina Tomograph III, Heidelberg, Germany). During the 3-year observation the patient reported symptoms mainly in the right eye. Slit-lamp examination revealed endothelial changes, much more pronounced in the right eye. Examination by the AS-OCT Visante showed hyperreflective dots within the right corneal endothelium. In order to assess endothelial cell morphology, analysis using corneal confocal microscopy in vivo was performed. Scans revealed presence of single endothelial deposits and severe cell changes of different morphology in both eyes. In the right eye, less pronounced changes of the polymorphic structure—polygonal guttas in different stages, linear and branched loss with "nuclear-like" formations and accompanying sediments. In the left eye, severe homomorphous polygonal "guttas-like" changes with "nuclear-like" formations were observed. Endothelial cysts' features were dynamically changing during follow-up time with different effects on the patient's clinical state. Corneal confocal microscopy allows accurate imaging of the endothelial cells and their detailed characteristics. Structural changes within the endothelial cells are not always proportional to visual acuity and slit-lamp image. The presented case is an example of an unusual corneal endothelial syndrome with probably nondystrophic background due to observed dynamic state with regressive tendency.